Resilience of Female Floating Market Traders in Lok Baintan, South Kalimantan During the Covid-19 Pandemic - Muhammad Hafidz Ilmi (Islamic Economics and Business Faculty of UIN Antasari, 2023)
This qualitative study investigates the resilience of female floating market traders in Lok Baintan, South Kalimantan during the Covid-19 pandemic. The research aims to understand the impact of the pandemic on these traders' income and their ability to adapt to the challenges posed by government policies and restrictions. The study employs interviews, observations, and documentation as data collection techniques and purposive sampling to select 10 female traders as research participants. The findings reveal that the pandemic has had varying effects on the traders, with some experiencing a moderate level of influence while others faced a strong level of impact, leading to resignations. Factors like adherence to government regulations and belief in fate play a role in the resilience of these traders. The paper contributes to the existing literature on resilience and the economic impact of the Covid-19 pandemic in Indonesia.Studi kualitatif ini mengeksplorasi ketahanan pedagang perempuan pasar terapung di Lok Baintan, Kalimantan Selatan selama pandemi Covid-19. Penelitian ini bertujuan untuk memahami dampak pandemi terhadap pendapatan pedagang ini dan kemampuan mereka dalam beradaptasi dengan tantangan yang ditimbulkan oleh kebijakan pemerintah dan pembatasan. Studi ini menggunakan wawancara, observasi, dan dokumentasi sebagai teknik pengumpulan data, serta purposive sampling untuk memilih 10 pedagang perempuan sebagai partisipan penelitian. Temuan penelitian mengungkapkan bahwa pandemi memiliki efek yang bervariasi pada para pedagang, di mana beberapa mengalami pengaruh sedang sementara yang lain menghadapi dampak yang kuat, hingga mengakibatkan keputusan untuk berhenti berdagang. Faktor-faktor seperti kepatuhan terhadap regulasi pemerintah dan keyakinan pada takdir berperan dalam ketahanan para pedagang ini. Riset ini memberikan kontribusi pada literatur yang sudah ada tentang ketahanan dan dampak ekonomi pandemi Covid-19 di Indonesia.